Chores completion encourager app for children using games based learning / Nurul Adilah Fasiha Abdul Rahman - Abdul Rahman, Nurul Adilah Fasiha (Faculty of Computer and Mathematical Sciences, 2015)
Daily chores can be introduce to children as early as preschoolers. Preschoolers should be encourage to perform their own chores since they are reluctant to complete their chores, they do not know the outcomes of undone chores and they are not interested to do the chores if they are just told to do so. The purpose of this project is to motivate preschoolers in the range of 5 until 6 years old to be more responsible for their own chores. The preschoolers will be motivated by marks and level achieved in the game. Games Based Learning is the best way to encourage the preschoolers since it can attract the preschooler’s attractions to play the games and complete the chores. In addition, the combination of several techniques is used to design the applications such as Level Setting Principle, Task Introducing, Arrangement of Task, Usage of Colors and Object, Moving to Next Task, and Gameplay Principle so that it will reach children’s expectations in learning through gaming . Other than that, this applications will be implemented in android since it is android based system because preschoolers are proved to be more attracted to play the games through mobile phones. Methodology used to develop this applications is Rapid Applications Development (RAD). The result from usability testing shows that the applications is beneficial to 80% of selected preschoolers. The other 20% of the preschoolers do not performing their chores after play the games because they found out that the games is just for fun and do not give impact for them. This project may be upgrade from time to time by adding new features such as more chores can be perform in the applications and more multimedia element such as audio and agent so that in the future it will be more interesting and helpful.